The 2022 country specific recommendations in the social field: Quo vadis, EU recovery? An overview and comparison with previous European semester cycles - Silvia Rainone (European Trade Union Institute (ETUI), 2022)
This report provides an analysis of the 2022 Country Specific Recommendations (CSRs) made by the Council, on a proposal by the Commission, concerning social and labour policies. Account is taken of the main new features of this Semester cycle, notably the integration of the European Semester in the NextGenerationEU strategy and the ongoing energy crisis. The social CSRs are examined from both a thematic and a country perspective. The inclusion of data from previous years' ETUI analysis allows for a comparative outlook and to grasp the overall evolution of the approach of the CSRs to national social and labour policies. Overall, it emerges that, similar to the CSRs adopted in 2020, this year's recommendations do pay attention to the social dimension. However, the analysis also indicates that there is renewed emphasis on the sustainability of public finance and the macroeconomic situation of the countries. This is reflected in recommendations to limit public spending and social investment, especially in pension systems and long-term care.
Keywords: 330